PENERIMAAN MASYARAKAT TERHADAP PENGGUNAAN GAS LPG DI DESA DUSUN TUA KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Ikhwani, Nur; Rosaliza, Mita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Dusun Tua Village, Kelayang Sub-district, Indragiri Hulu District with the problems: (1) How is the level of community acceptance on the use of LPG gas in Dusun Tua Village, Kelayang Sub-district? (2) What factors influence the community to choose or refuse the use LPG gas in Dusun Tua Village, Kelayang Sub-district? The objective of this research was to find out the level of community acceptance on the use of new innovation namely LPG gas and to find out whether the community accept or refuse the new innovation namely LPG gas as a substitute of kerosene and firewood for cooking fuel. This was a descriptive quantitative research. The population of this research was the citizens of Dusun Tua Village, Kelayang Sub-district, with the sample of 58 respondents. In collecting the data, this research used observation and questionnaire techniques. After conducting the research, it was obtained that there were 48 respondents using LPG, 1 respondent using kerosene, and 9 respondents using firewood. Based on the results, it was obviously seen that LPG gas was the most cooking fuel used by the community. It indicated that the Community of Dusun Tua Village, Kelayang Sub-district, received LPG gas as a new innovation. Whereas, based on the curve of LPG acceptance level in Dusun Tua Village, Kelayang Sub-district, there were no groups of innovators and pioneers. Instead, it was found that there were 3 respondents as the early followers, 36 respondents as the final followers, and 9 respondents as conservative followers.Keywords: Innovation, Acceptance, LPG Gas, Indragiri Hulu Dusun Tua